PENGEMBANGAN MODEL CREDIT SCORING UNTUK PROSES ANALISA KELAYAKAN FASILITAS KREDIT PEMILIKAN RUMAH (STUDI KASUS DI BANK BUKOPIN) - Dwi Andhayani; Harianto MS; Noer Azam Achsani (School of Business, Bogor Agricultural University (SB-IPB), 2009)
Analysis of the parameters used in the model skoring E-Flow, which has 14 parameters, namely the interest rate, the amount of insurance, age / age, type of work, penghasilkan per month, the average balance, savings in the bank, the percentage of money face, the type of collateral, documents of ownership, broad building, Burden debt ratio, bad debts in the information and the position of BI / debtor position. In addition to design a credit scoring model application, a skoring system will have a very full prepayment behavior scoring and scoring. Accordingly at this time until a new stage in the application of determining the credit scoring model, to further research can be done model behavior prepayment scoring and scoring on the credit facility.